1983
DOI: 10.1620/tjem.140.59
|View full text |Cite
|
Sign up to set email alerts
|

Natural and antibody-dependent cellular cytotoxicity of polymorphonuclear leukocytes.

Abstract: Cytotoxic activity of polymorphonuclear leukocytes (PMN) in the peripheral blood of patients with various diseases was demonstrated to K562 cells (natural cytotoxicity, NC) and the antibody-coated P815 cells (antibody-dependent cellular cytotoxicity, ADCC, using a 51Cr-release method. The NC values of normal PMN were lower than those of normal lymphocytes with mean values of 5.0% and 30%, respectively. The NC values of patients' PMN were also lower in malignancy, chronic hepatitis and connective tissue disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Later, Takasugi et al showed that peripheral blood PMN possessed nonspecific cytotoxicity against various cultured human tumor lines,17 and Clark et al reported that peroxidase systems present in inflammatory cells,18 and especially the PMN,19 were cytotoxic for mouse lymphoma cells. Over the following years, a large number of reports showed that PMN had cytotoxic and/or cytostatic effects on cancer cells in vitro 20–95. Weiss and Slivka showed that the ability of PMN to destroy human T lymphoblasts was at least the same as that of monocytes,35 and in mice, PMN were found more cytotoxic to several tumors than were macrophages 53.…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Takasugi et al showed that peripheral blood PMN possessed nonspecific cytotoxicity against various cultured human tumor lines,17 and Clark et al reported that peroxidase systems present in inflammatory cells,18 and especially the PMN,19 were cytotoxic for mouse lymphoma cells. Over the following years, a large number of reports showed that PMN had cytotoxic and/or cytostatic effects on cancer cells in vitro 20–95. Weiss and Slivka showed that the ability of PMN to destroy human T lymphoblasts was at least the same as that of monocytes,35 and in mice, PMN were found more cytotoxic to several tumors than were macrophages 53.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Many of the reports listed in Tables I and II discuss the anticancer effect of PMN via ADCC,27, 41, 46, 50, 64, 83, 116, 120, 122–126, 128, 129, 131–177 and many provide direct evidence of this antibody‐mediated antitumoral role of PMN in vitro. The first reports were published in 1974 and 1975 by Gale and Zighelboim 131, 132.…”
Section: Antibody‐dependent Tumor Killingmentioning
confidence: 99%